2017
DOI: 10.1111/1471-0528.14742
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes in patients with uterine fibroids treated with ultrasound‐guided high‐intensity focused ultrasound

Abstract: Objective To investigate the effect of high-intensity focused ultrasound (HIFU) ablation for uterine fibroids on pregnancy.Design A retrospective observational study.Setting Department of Gynaecology in a single centre in China.Population Patients with uterine fibroids who wish to become pregnant.Methods Patients with uterine fibroids who wished become pregnant and have children, were treated using HIFU from April 2011 to March 2016 at Chongqing Haifu Hospital. Pregnancy outcomes were analysed.Main outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 13 publications
3
51
1
3
Order By: Relevance
“…In another study, where 51 patients conceived after MRgFUS treatment of uterine fibroids, the vaginal delivery rate was 64% [34]. Compared to the average interval of 16.0 ± 8.7 months between myomectomy and pregnancy, the time between HIFU and conception was significantly shorter [33][34][35]. Therefore, for patients with multiple fibroids who wish to conceive, HIFU is preferable to myomectomy because it causes less damage to the myometrium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, where 51 patients conceived after MRgFUS treatment of uterine fibroids, the vaginal delivery rate was 64% [34]. Compared to the average interval of 16.0 ± 8.7 months between myomectomy and pregnancy, the time between HIFU and conception was significantly shorter [33][34][35]. Therefore, for patients with multiple fibroids who wish to conceive, HIFU is preferable to myomectomy because it causes less damage to the myometrium.…”
Section: Discussionmentioning
confidence: 99%
“…The C-section rate seems to be high in this study: 56 (78.9%) cases had C-section. However, 50 of them had caesarean sections for social reasons [33]. In another study, where 51 patients conceived after MRgFUS treatment of uterine fibroids, the vaginal delivery rate was 64% [34].…”
Section: Discussionmentioning
confidence: 99%
“…A study that assessed the clinical outcomes of HIFU in patients with uterine fibroids using the UFS-QOL questionnaire indicated that HIFU is a cost-saving and effective treatment option for uterine fibroids [32]. Zou et al noted that 19.2% of patients (78/406) who had uterine fibroids and had a history of abnormal pregnancies became pregnant after HIFU treatment [33], suggesting that HIFU could be a treatment option for infertility. More recently, the use of HIFU has extended to treatment of patients with [36].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 50 patients, 8 (16%) were diagnosed with primary infertility, and 42 (84%) were diagnosed with secondary infertility. In the LE group, the average age of patients was 35 years (IQR [31][32][33][34][35][36][37][38]. Before LE treatment, their average uterine volume was 148.3 cm 3 (IQR 73.5-202.1).…”
Section: Patients' Characteristicsmentioning
confidence: 99%
“…The data on the long-term impact of HIFU therapy on fertility are still insufficient, but recent report by Zhou et al [21] has shown promising results. These Authors investigated pregnancy outcomes following the HIFU treatment in one institution over 5 years.…”
Section: Side Effects/complications Of Mri Guided Hifu Therapymentioning
confidence: 99%